Analisis Pengendalian Kualitas pada Proses Coating Project Fabrikasi Metal Ducting MBI di PT. Swadaya Graha Menggunakan Metode FMEA - Melanida Agustin; Akmal Suryadi (International Forum of Researchers and Lecturers, 2024)
. This research was conducted to analyze the quality of the coating process at PT Swadaya Graha using the Failure Mode Effects Analysis (FMEA) method. Primary and secondary data collection was carried out in this research. The research results showed that there were five types of defects, namely polishing marks, orange peel, dustpray, sagging and cracking. Based on the FMEA method, the defect rating is determined based on the resulting cumulative percentage value where the highest value is obtained for orange peel defects at 41.7%. This defect was analyzed and it was found that one of the causal factors was the incorrect application of the spreading rate. This factor is obtained from an RPN value of 120. From this research it can be concluded that the FMEA method can be used as a tool to minimize defects in the coating process and analyze improvements that should be prioritized..